Correlação entre imagem de ressonância magnética e imagem por microscopia de hipocampos de pacientes com epilepsia do lobo temporal mesial com esclerose de hipocampo - Gonçalves, Ariadne Sanches [UNIFESP] (2010)
The mesial temporal lobe epilepsy (MTLE) is the most frequent form of refractory epilepsy in adults. The most common pathological finding is the hippocampal sclerosis (HS), characterized by neuronal loss and gliosis, especially in the Sommer sector (CA1 and prosubiculum) and the hilar region (CA4), with relative preservation of CA2, subicullum and granular layer of DG. The diagnosis of HS by MRI is characterized by an increased volume and/or decreased hippocampal signal on T2 weighted or FLAIR sequence, and may be accompanied by changes in shape and internal structure of the hippocampus. This works aims to achieve the co-registration of images obtained by magnetic resonance and histopathological findings in sclerotic hippocampi of MTLE patients. We used hippocampi of MTLE patients subjected to surgery and necropsy cases (controls). Firstly, control hippocampi were used for technical adjustments of the protocol, which was than applied to MTLE cases. 3D volumes were obtained from histological and MR images. The co-registration of theses volumes was obtained by using reference points (landmarks). The mean number of landmarks in control cases was 16 (sixteen) and, in sclerotic hippocampus, tests were made using 9, 16 e 32 points. Based on the results, it was possible to establish common spatial coordinates for histological and MR images, in order to allow point-to-point correlations. Satisfactory results were obtained with sclerotic hippocampi, although with less quality